2003
DOI: 10.2165/00023210-200317120-00003
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Opioids for Combined Spinal-Epidural Analgesia during Labour

Abstract: In <25 years, intrathecal administration of opioids (i.e. spinal analgesia) has evolved from an experimental model into an important therapy for obstetric analgesia and anaesthesia. A small dose of opioid delivered into the CSF provides almost immediate relief from labour pain with minimal risks to the mother and fetus. Careful attention, and prompt treatment when needed, can ameliorate the adverse effects of fetal bradycardia, respiratory depression and pruritus. The major limitation of intrathecal opioids fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 139 publications
2
28
0
Order By: Relevance
“…On the contrary, the above mentioned Cochrane Review found higher rates of these two side effects when pain relief was provided with epidural analgesia; this could be due to the fact that our study included a smaller number of women. Remarkably, pruritus has been even defined as the "hallmark of intrathecal opioid", reaching an incidence >80% [22]. Accordingly, in our study pruritus was also more common in CSEA group.…”
Section: Discussionsupporting
confidence: 62%
“…On the contrary, the above mentioned Cochrane Review found higher rates of these two side effects when pain relief was provided with epidural analgesia; this could be due to the fact that our study included a smaller number of women. Remarkably, pruritus has been even defined as the "hallmark of intrathecal opioid", reaching an incidence >80% [22]. Accordingly, in our study pruritus was also more common in CSEA group.…”
Section: Discussionsupporting
confidence: 62%
“…The use of fentanyl in the spinal canal may be questioned since intrathecal fentanyl has been known to produce pruritus. [19][20][21][22] While the incidence of pruritus was related to the intrathecal dose of fentanyl in one study, 22 this was not the case in another. 21 However, both studies showed pruritus to be common at intrathecal doses as low as 5 or 10 µg (33-75%).…”
Section: Discussionmentioning
confidence: 89%
“…While systemic administration of morphine is used in opioid therapy targeting chronic pain, intrathecal administration of MOP agonists has been one major breakthrough in pain management during the past three decades and has since become the most common way of inducing analgesia in obstetrics and for surgery. 10,12 However, spinal administration of MOP agonists is most often accompanied by the unwanted itch sensation (pruritus) in patients. 12,13 In obstetrics, pruritus has been a long-term concern that requires the use of antipruritic drugs.…”
Section: ■ Limitations Of Using Mop Agonistsmentioning
confidence: 99%